Avaliação de borregas das raças Corriedale e Texel, esquiladas ou não esquiladas, terminadas em confinamento - Rodrigues, Ana Clara Trindade (2021)
This study aimed to evaluate the physiological variables, consumption, ingestive behavior, production characteristics (chapter I), carcass characteristics, non-carcass components and meat quality (chapter II) of Corriedale and Texel ewe hoggets, shorn or non-shorn, finished in feedlot. Forty-four animals were used, 22 of the Corriedale breed and 22 of the Texel breed, where 11 animals of each breed were shorn. Texel had higher ocular temperature (TO) and skin temperature (TS) (P≤0.05), while those not shorn had higher respiratory frequency (Freq.Resp.) and lower wool temperature (TW) than shorn. As for the ingestive behavior, Texel spent more time in rumination (RUM) and total chewing (TCT) activities and spent less time in idleness (IDLENESS) compared to Corriedale. Sheared hoggets remained standing longer (ST) and less time lying down (LD) than those not shorn. The dry matter (DMI) and nutrient intake was not influenced (P>0.05) by the breed of hoggets. On the other hand, shorn hoggets showed superiority (P≤0.05) for dry matter (DMI), organic matter (OMI), crude protein (CPI), neutral detergent fiber (NFDI), acid detergent fiber intakes. (ADFI) and total digestible nutrients (TDNI), when expressed in kg/day, % of LW and g/kg LW0.75. In the productive characteristics, Texel showed superiority in relation to the average daily weight gain (DWG) and, as a consequence, in the live weight at slaughter (LWS), in addition to presenting a better body condition score at the end of the experiment (BCSE). The shorn had higher BCSE than the unshorn. Regarding the characteristics of the carcass, non-carcass components and meat quality, Texel were higher (P≤0.05) in the variables slaughter live weight (SLW), hot carcass weight (HCW), cold carcass weight (CCW), hot carcass yield (HCY), cold carcass yield (CCY), carcass compactness index (CCI), carcass conformation (CONF), neck weight (NECK), pallet (PAL), leg (LEG), besides % of leg. The Corriedale were higher in the rib variable (RIB) in %. The shorn were superior in HCW, CCW, HCY, CCY, CCI, in addition to NECK, RIB in kg and RIB in %. Unshorn ones had the highest % of LEG. In non carcass components, Corriedale were higher in kg and in % for external organs (ExtOr), while. The unshorn had higher weight and % of ExtOr, while the shorn had higher weight and % of gastrointestinal organs (GiOr). In the evaluation of pH and temperature (Temp), the Texels had the highest pH0, whereas the shorns had the highest Temp0. In the instrumental evaluation, Texels had higher losses on thawing (HLT) and losses on cooking (LC), while Corriedale had higher water retention capacity (WRC). The shorn showed higher LC, there was an interaction between race x system for LC. When finished in a feedlot system, Texel ewe ewes show better performance than Corriedale ewes. Shearing provides benefits in the termination of feedlot ewes.